RENEWABLE ENERGY SOLUTIONS FOR TOURISM - Karabuğa, Arif; Yakut, Melik Ziya; Yakut, Gamze; Selbaş, Reşat; Üçgül, İbrahim (European Scientific Journal, ESJ, 2015)
This study aimed to investigate the importance of renewable energy sources usage in tourism which has a significant market power in world economy. Tourism has a big contribution to regional development and also some cons on environmental issues. To reduce the negative aspects on environment and increase the financial savings of tourism industry, renewable energy has a vital priority. Renewable energy will align the hotel areas with concept of green tourism. Financial savings through this energy also has been provided in that study. This paper also suggests an analysis for suitable sources of renewable energy usage in hotels with a sample practice.